KESALAHAN STRUKTUR SEMANTIS 補助動詞 - Dance Wamafma (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
The standard structure of the verbs くれる  and あげる is, "... は....に....を ... verbs くれる/あげる" e.g. in '先生は 弟にプレセントを買ってくれた'。  The above sentence  holds several provisions that are rarely observed by Japanese language learners in Indonesian mother tongue. One aspect that is rarely noticed  is the social status of the subject, recipient (dative), and predicate.  The social status of the person as a Giver/G is  先生(lecturer), who is superior to the Speaker/S (someone as a 私who is having a conversation with his classmates).  The receiver/R dative (receiver) is inferior to S,G and has a blood relationship to S.  Thus,  the used verb isくれる。  The explanation as above was raised in a questionnaire to see students' understanding of these cases.   From  the results of the  analysis questionnaire,  several errors were found in  the form of interference with the mother tongue structure,  difficulty determining verbs that are in harmony related to social relations G, R, S, and H (hearer) . Errors also occur in the gradation of speech acts according to the keigo rule and John Love's rule (1965: pg. 57-78) which essentially contains the sentence やりもらい。 So it is necessary to reorganize the teaching of the verb  'give' or which should also touch the social status of the  やりもらいsentence.Keywords:G (Giver); R(Receiver); S(Speaker); inferior; superior